Diante da imagem: fundamentos epistemológicos para os processos pedagógicos - Batista, Jordana Rodrigues (2022)
We are daily confronted by multiple images reproduced by different digital devices. Nevertheless, the research on screen aimed to understand the process of knowledge construction through the imagery reading of these techno-images. Though, the research was divided into two articles, the first one brings an epistemological theoretical basis based on the studies of Vilém Flusser (2002, 2012) and Didi-Huberman (1998, 2013), and the second one has as main objective to bring the practical representation of technical images in the form of memes as an instrument of pedagogical application for public schools. In this way, the following specific objectives were proposed: to conceptualize technical image and dialectical image in Flusser (2002, 2012) and Didi-Huberman (1998, 2013) and to identify the epistemological foundations arising from the presence of these images in pedagogical processes. Therefore, we obtained as a final product a pack of memes that inspire the elaboration of didactic sequences in order to contribute to the pedagogical process.